Lexemic Conversion in Indonesian - I Dewa Putu Wijana (Deskripsi Bahasa, 2021)
This paper is intended to describe various possiblities of Indonesian lexemic conversion to other lexemes that belongs to other word classes but they are still semantically included in the same sememes. By observing data gathered intuitively as an Indonesian native speaker, and their possibilities of becoming members of other word classes, it is found that there are many Indonesian vocabularies have potentials to be transposited to othar word classes through conversion processes. Indonesian verbs and nouns tend to have greater possibilities to convert to other categories than the other parts of speech. All of these phenomena suggests that conversion processes are essentially constituting the unlimited human thinking and the limited language as the expression medium.